HUBUNGAN ANTARA PERSEPSI MASYARAKAT DAN MINAT SISWA MELANJUTKAN STUDI DI MTs - Asniati Asniati (Institut Agama Islam Negeri Palopo, 2018)
This study aims to determine the public perceptions around the Madrasah Tsanawiyah Sabilit Taqwa of Margomulyo Village, Tomoni Timur Subdistrict, East Luwu Regency, and to find out the interest of students to continue their study at Madrasah Tsanwiyah Sabilit Taqwa, Margomulyo Village, Tomoni Timur Subdistrict, East Luwu Regency, and to find out the significant relationship between people's perceptions and the interest of students continuing their studies at Madrasah Tsanawiyah Sabilit Taqwa. This research use descriptive quantitative and inferential research with ex-post facto research design that is symmetrical. The total population is 2037 consisting of 2003 people and class VII students as many as 34 students by sampling uses probability sampling and simple random sampling technique so that it is set to 100 societies while the determination of the sample for students with a total sampling technique so that 34 madrasah students class VII. The instrument used in this study was questionnaires, while the statistical analysis technique used was using the SPSS program ver. 20 for Windows.The results of SPSS data processing obtained an average score of public perception of 78.23 with a standard deviation of 7.477. Likewise, the average score of student interest is 79.50 with a standard deviation of 5,040. Based on the results of the study showed that public perceptions have a very strong relationship with the interest of students continuing their studies at Madrasah Tsanawiyah Sabilit Taqwa Margomulyo Village, Tomoni Timur District, East Luwu Regency with a significance level is 0.00 and the correlation coefficient level is 0.816. This shows that between public perceptions and the interest of students continuing their studies at Madrasah Tsanawiyah Sabilit Taqwa has a very strong and positive relationship